Metabolites analysis for cold-resistant yeast (Wickerhamomyces anomalus) strains own antioxidant activity on cold stored fish mince. (15th January 2020) - Xu, Lina; Guo, Weidan; Liu, Weicong; Fu, Xiangjin; Wu, Yue; Luo, Feijun; Xu, Youzhi
Highlights: W. anomalus exhibited strong viability at 4 °C. W. anomalus eliminated TBARS in fish mince effectively. W. anomalus produced large quantities of saccharides own prebiotic activity. W. anomalus produced many metabolites with antioxidant or antibacterial activity. Abstract: The effect of eight cold-resistant yeast strains (J3, J7, J8, J9, J12, J15, J18, and J25) of Wickerhamomyces anomalus on the lipid oxidation of cold stored fish mince (4 °C) were investigated. And the metabolites of these yeast were determined with gas chromatography–mass spectrometry. These strains could effectively inhibit the increase of hydroperoxides value (p < 0.05), and the inhibiting rate was positively correlated with the content of isolongifolene, xylitol, turanose, thymol-glucoside, and uridine. Especially, the J3, J7, J8, J9, J12, and J18 could eliminate a large part of thiobarbituric acid reactive substances (TBARS) (p < 0.05), the eliminating rate was proportionate to the aldehyde dehydrogenase activity. Several bacteriostatic metabolites were detected: thymol-glucoside, 2-phenylethanol, cedro, and 2, 4-bis (1, 1-dimethylethyl) phenol. In addition, W. anomalus produced many metabolites with fruit and floral notes. In conclusion, cold-resistant W. anomalus strains own antioxidant activity were potential new bio-preservatives in the cold storage of muscle products.